ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA YANG TERKENA PEMUTUSAN HUBUNGAN KERJA AKIBAT DAMPAK COVID-19 (STUDI PENELITIAN PADA KANTOR DINAS KETENAGAKERJAAN KOTA BATAM) - Anggun Anggun; Darwis Darwis; Lia Fadjriani (Ensiklopedia of Journal, 2023)
The selection of the title of the thesis is about "Selecting the title of the thesis on "Juridical Analysis of Legal Protection for Workers Affected by Termination of Work Due to the Impact of COVID-19 (Research Study at the Batam City Manpower Office). The massive and rapid spread of the corona virus 19 in Indonesia has disrupted the Indonesian economy. The impact of this pandemic is felt by workers as the community group most affected by the different conditions and needs of each type of work with this pandemic. One of the sectors most affected by the coronavirus pandemic, the impact of the pandemic on the lives of different people is work. The spread of the corona virus in almost every region of Indonesia is the ability of employers to fulfill performance, productivity, company finances, and workers' normative rights, namely operational needs, including payment of wages. hear. In addition, the existence of work restrictions and the encouragement to work from home creates new problems for companies, because not all types of work are carried out by remote workers. The negative impact of this pandemic is that many companies cannot operate properly so that many companies suffer losses and not a few are forced to close their companies which in the end has an impact on unilateral termination of employment (PHK) in many companies. Therefore, knowledge of the legal protection for termination of employment is needed from the perspective of the Manpower Act. The results in this study indicate that (1) the legal arrangements in the Implementation of Termination of Employment that occur in the community in Batam City are Government Regulation Number 35 of 2021 concerning Work Agreements for Certain Time, Outsourcing, Working Time and Rest Time, and Termination of Employment (2) the inhibiting factor is the Inhibiting Factor: there is still an apathetic attitude and character of PKH participants. There are still PKH Participant data that are not accurate, room capacity, facilities and infrastructure are limited.